Evaluation of the metaphorical image in architecture - Al-jamel, Ali Haidar; Minouna, Naam Behnam (Iraqi Journal of Architecture and Planning, 2009)
The metaphorical image represented in the architectural works was subjected to evaluation by different social sectors perceiving them in the society. Despite the diversity in the studies related to metaphorical image. In addition, the special standards forwarded for metaphorical image were dependent on selective formula as they were conjugated with the cultural context to which the critic belongs giving such interpretations. These studies.could not formulate a theoretical framework comprised cultural contexts. Its methodology concentrated ontheconstructionof atheoretical framework, the isolation of the variables related its main aspects, the clarification of its measurements and the performance of a selected field study which includes the main aspects of the evaluation process. This papers aims to determine and describe factors influencing evaluation of the metaphorical image in architecture according to certain architectural patterns to specimen from Iraqi environment. The framework included aspects represented by the metaphorical process, perception and evaluation. Using a special methodology the research hypotheses were checked and the data were processed using the computer software SPSS for statistical analysis.